(3GdCSQI(B: (3GdJdaRjhf hGdeOQSI aj HdOI GfUGQjIs - (3YjSi, QGfjG CMeOs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3eYgO GdYdhe GdGLJeGYjIs, 2015)
(3JgOa GdOQGSI Edi EXgGQ GdJaGYd Hjf GdJdaRjhf hGdeQGgbjf Vef GdeLGd GdCSQj hYdi GdcTa Yf BdjGJ GdJaGYd hedehSjJgG hCfeGWgG, hOQGSI JCKjQ GdJdaRjhf aj eQMdI GdeQGgbI, heYQaI GdYdGbI Hjf GdJdaRjhf hGdeQGgbjf OGNd GdeLGd GdCSQj(B. (3EYJeOJ GdOQGSI Ydi efgL GdJhKjb ef NdGd GdEWdGY Ydi GdcJH hGdeQGLY hGdCHMGK GdLGeYjI hGdOQGSGJ GdeJYdbI HGdehVhY, hefgL GdGSJWdGY GdejOGfj GdPj GYJeO Ydi GdedGMXI GdeHGTQI, GdebGHdI, hGdGSJeGQI(B. (3hEbJUQ eLJeY GdOQGSI Ydi HdOI CfUGQjI bVGA UjOG, hTedJ GdYjfI (B150 (3WadkG hWadI eQGgbjf Hjf GdaFGJ GdYeQjI (B12 (3Edi (B17 (3SfI(B. (3HjfJ GdfJGFL Cf GdJdaRjhf jfJTQ EfJTGQG hGSYG aj HdOI CfUGQjI, hjJNPg GdeQGgbhf hGdeQGgbGJ cCSGS ddJSdjI HMjK jhGXHhf Ydi eTGgOI GdHQGeL GdJQajgjI hGdeSdjI HTcd NGU, hdG Jhdi CgejI aYdjI ddHQGeL GdKbGajI, GdGLJeGYjI, GdOjfjI hGdSjGSjI(B. (3ceG jSGge GdJdaRjhf aj RjGOI hJjQI GdJZjQ aj GdNUGFU GdKbGajI hGdSeGJ GdELJeGYjI hGdeYGjjQ GdSGFOI dOi GdeQGgbjf hGdeQGgbGJ GdehLhOjf aj GdeLGd GdCSQj, hceG jSGge HTcd CSGSj aj JHOjd WHjYJgG(B. (3hjOaY GdJdaRjhf fMh JYGXe GdfRYI GdGSJgdGcjI YfO GdeQGgbjf hGdeQGgbGJ ef NdGd GdMedGJ GdOYGFjI hGdEYdGfjI GdJj JMJd MjRG cHjQG ef ChbGJ GdeTGgOI, hJbOe feGPL KbGajI(B- (3ESJgdGcjI LOjOI Ydi BdjGJ GdJfTFI GdJj GYJGOhG YdjgG aj eLGdGJge GdCSQjI(B. (3cPdc jdYH GdJdaRjhf OhQG eMhQjG aj HdhQI GdUdGJ GdELJeGYjI Vef GdCSQI, hHjfgG hHjf GdCSQ GdCNQi OGNd GdeLJeY GdeOQhS, hHQhR fRYGJ aQOjI ZjQ eSHhbI(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Ansariye; Ansariye; Milieu Socio-Culturel; Socio-Cultural Milieu; (3GdhSW GdKbGaj GdGLJeGYjs; (3GfUGQjIs